The Nation’s Soul and Motherhood: Conceptualizations of the State as a Body or Person in Slavic L1-ELF Responses - Andreas Musolff (Slavia Meridionalis, 2025)
The Nation’s Soul and Motherhood: Conceptualizations of the State as a Body or Person in Slavic L1-ELF Responses One of the key-metaphors in conceptualizing national identity is that of the nation as a body or a person. Nation-embodiment and -personalization have had a long conceptual history spanning more than two millennia and still figure prominently in present-day political discourse. Both the target and source-domains have changed considerably over time, so it may be asked in which sense the metaphor has remained the same. New evidence from an interpretation survey conducted in 30 countries in 2011–2020 suggests that this conceptual metaphor functions at two levels, i.e., 1) an abstract general mapping and 2) pragmatically enriched “scenarios” that lead to creative applications. As evidence for such scenarios, the article presents data from Slavic L1 survey samples that illustrate the interplay between the matrix mappings and innovative meaning aspects that are grounded in culture-specific discourse traditions.   Dusza narodu a macierzyństwo. Konceptualizacje państwa jako ciała lub osoby w anglojęzycznych (ALF) odpowiedziach natywnych użytkowników języków słowiańskich Jedną z kluczowych metafor w konceptualizacji tożsamości narodowej jest naród jako ciało lub osoba. Ucieleśnienie i personalizacja narodu są obecne w historii pojęć ponad dwa tysiąclecia i nadal zajmują ważne miejsce we współczesnym dyskursie politycznym. Zarówno domena docelowa, jak i źródłowa uległy znacznym przeobrażeniom na przestrzeni czasu, co rodzi pytanie, w jakim sensie omawiana metafora pozostała tożsama. Nowe dowody (pochodzące z badania interpretacyjnego przeprowadzonego w 30 krajach w latach 2011–2020) sugerują, że ta metafora konceptualna funkcjonuje na dwóch poziomach, tj. 1) abstrakcyjnego ogólnego mapowania i 2) pragmatycznie wzbogaconych „scenariuszy”, które prowadzą do kreatywnych zastosowań. Jako dowód na istnienie takich scenariuszy, w artykule przedstawiono dane z prób ankietowych wśród użytkowników języków słowiańskich, które ilustrują wzajemne oddziaływanie na siebie mapowania baz doświadczeniowych i innowacyjnych aspektów znaczeniowych, które są zakorzenione w specyficznych dla danej kultury tradycjach dyskursywnych.